2017
DOI: 10.18632/oncotarget.21625
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of Bax/Bcl-2 ratio and onset of caspase-3/7 activation induced by derivatives of Justicidin B in human melanoma cells A375

Abstract: Diphyllin and its derivatives are well known cytotoxic natural products structurally related to the anti-cancer drug podophyllotoxin. We here study their structure-activity relationship upon human melanoma cells for first time. To this end, human melanoma A375 cells were incubated with Justicidin B and its 4-methoxylated or 4-glycosylated derivatives to evaluate their selective cytotoxicity and study their effects on cell cycle distribution, caspase activation, apoptosis induction using Annexin V-FITC/PI stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…When Bcl-2 is relatively predominant in cells, Bcl-2 will form a heterodimer with Bax, thus inhibiting apoptosis. However, when Bax is predominant in cells, Bax itself will form the homodimer, thus promoting apoptosis (16,17). Therefore, the Bax/Bcl-2 ratio has important significance for the occurrence and degree of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…When Bcl-2 is relatively predominant in cells, Bcl-2 will form a heterodimer with Bax, thus inhibiting apoptosis. However, when Bax is predominant in cells, Bax itself will form the homodimer, thus promoting apoptosis (16,17). Therefore, the Bax/Bcl-2 ratio has important significance for the occurrence and degree of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the high value and closeness of cross-validated regression-coefficient (Q 2 cv ) to the regression-coefficient (R 2 ) showed that the model was not over-fitted. The high R 2 pred as shown in the model explains that the generated model can provide good and valid predictions for the new compounds. A good and acceptable QSAR model must obey the following criteria: regression-coefficient (R 2 ) and adjusted regression-coefficient (R 2 adj) values close to one.…”
Section: Qsar Model and Validationmentioning
confidence: 85%
“…The coefficient of determination cR 2 p for Y-randomization is another parameter calculated which should be greater than 0.5 for passing this test as in Eq. (6): cR 2 p is Coefficient of determination for Y-randomization, R is the coefficient of determination for Y-randomization and R r is average 'R' of random models.…”
Section: Qsar Model Development and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, although therapeutic options are now better for patients with advanced melanoma than they were a decade ago, there is still a need for developing new drugs targeting melanoma, and a variety of approaches are still explored, from evaluating new targets (11) to exploring new delivery systems for old compounds (12). SK-MEL-5 is a human melanoma cell line derived from a metastatic axillary node of a young female patient, and is characterized by a high level of expression of the V600E mutation of B-Raf, of the wild-type N-Ras (13), as well as by relatively high levels of the ABCB1 transcript (14). This is unlike SK-MEL-2 melanoma cell line, which has wild-type B-Raf, but normal N-Ras (11).…”
Section: Introductionmentioning
confidence: 99%